Public Speaking Untuk Master of Ceremony : (Strategi Meningkatkan Skill Komunikasi Pada Mahasiswa) - kristina, dina (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
Everyone can speak, but not everyone including students have the skills to speak in public (public speaking). One example of public speaking activity that demands verbal and non-verbal communication skills is in the profession of presenter or more commonly known as MC (master of ceremony). In carrying out his duties, a MC will basically speak in front of a public audience and in practice, an MC not only speaks and reads the show but must be able to speak effectively and meaningfully. This research is to find out how the role of public speaking for the master of ceremony (MC) in improving verbal and nonverbal communication skills in students. The research methodology used is qualitative with the theory of phenomenology. Based on the results of the research, public speaking has an important role in improving communication skills and dealing with a variety of communication anxiety symptoms both verbal and nonverbal in the community of students of the Master of Ceremony (MC) at the Faculty of Communication Sciences of the University of Bhayangkara Jakarta raya